Determination of Optimal Dose of Gandharva Taila Bhrushta Haritaki Churna Ayurvedic Oral Preparation in the Management of Krura Koshtha (Severe Bowel Movements): A Randomised Clinical Trial Protocol - Nitin Ashok Dhawas; Vaishali Kuchewar; Mohnish Gokhale (Journal of Clinical and Diagnostic Research)
Introduction: In Ayurveda, Koshtha is defined as a bowel movement based on an individual’s basic constitution. There are three types of Koshtha-Mrudu (soft stool), Madhyam (moderate), and Krura (harsh or severe gastrointestinal nature). Individuals with Krura Koshtha are more prone to various diseases due to improper Koshtha Shuddhi. Hence, Koshtha Shuddhi (cleansing or purifying the gastrointestinal tract) is an integral part of treatment for most diseases. Virechan (therapeutic purgation or induced bowel evacuation) is advised for Koshtha Shuddhi. Need of the Study: The action of Anulomana Dravyas (the drugs that gently stimulate downward movement in the intestines to facilitate bowel evacuation) affects the entire gastrointestinal tract. Gandharva Taila Bhrushta Haritaki is recognised as the best Anulomaka. The recommended dose of Gandharva Taila Bhrushta Haritaki Churna is described as 5-10 grams at night. Therefore, the present study is planned to confirm the optimal dose of Gandharva Taila Bhrushta Haritaki Churna for appropriate Koshtha Shuddhi in individuals with Krura Koshtha. Aim: To determine the optimal dose of Gandharva Taila Bhrushta Haritaki Churna in the management of Krura Koshtha volunteers. Materials and Methods: This is a three-armed parallel interventional trial, will be conducted in the Kayachikitsa Outpatient Department (OPD) and Inpatient Department (IPD), Mahatma Gandhi Ayurveda College, Hospital and Research Centre, Salod (H), Wardha, Maharashtra, India, from July 2024 to July 2025. A total of 90 participants who meet the inclusion criteria will be identified and randomly enrolled in three groups: Group A, Group B and Group C. Gandharva Taila Bhrushta Haritaki Churna will be administered orally to Groups A, B and C in doses of 5 grams, 7.5 grams and 10 grams, respectively, for seven days, once at bedtime. Daily follow-up will be conducted to assess Koshtha Shuddhi. Data will be analysed using the Chi-square test to find significant differences between the three groups concerning categorical variables of the Bristol stool chart, with a significance level set at p-value <0.05.